Fatigue in sarcoidosis: American versus Dutch patients - de Kleijn, W.P.E.; Elfferich, M.D.P.; De Vries, et al., J. (Sarcoidosis, Vasculitis and Diffuse Lung Diseases, 2009)
Background: Fatigue is a major problem in sarcoidosis. Fatigue has mainly been examined in patients from the Netherlands. Objective: The aims of the study were to establish the prevalence of fatigue in US and Dutch patients and to determine whether fatigue was related to the common demographic and clinical parameters. Design: Two patients groups were studied: Dutch outpatients at Maastricht University Medical Center in the Netherlands (n = 121) and US patients at the University of Cincinnati Medical Center in the USA (n = 126). Both groups completed the Fatigue Assessment Scale. Clinical data were gathered from the patients’ medical files. Results: The prevalence of fatigue was similar in the US and Dutch patients, but more severe in the latter group. Fatigue was unrelated to demographic and clinical parameters in the total group. However, when examining the US and Dutch patients separately, fatigue was associated with age, extrapulmonary involvement and drug use in the US group. Conclusions: Dutch patients report more severe fatigue compared with US patients. Interestingly, fatigue was related to clinical and demographical parameters in the US patients, although no such relationships was found in the Dutch patients.